Motor bearing current detection for online bearing health monitoring - Huang, Jiaxin (Nanyang Technological University, 2023)
Compared to conventional monitoring techniques such as vibration monitoring or temperature monitoring, producing high frequency bearing current-based detection system can monitor the health conditions of the motor bearing. This method also offers significant economic savings and implementation advantages. Consequently, bearing current-based detection system has gained much attention significantly over the years in research. Moreover, according to a recent study, bearing faults can be categorized into two classes: single-point defects and generalized roughness. In this research paper, the bearing current-based bearing fault detection method is reviewed under this classification, in an attempt to provide a brief overview of the research in this area.